Sustainable Development Innovation “The Effect of Flexible HRM Behavior on SME Innovation” - Rodhiah Rodhiah; Nur Hidayah (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2021)
Through the results of the 2020 Higher Education grant research, shows the need for sustainable innovation development in SMEs through the development of the competence of creative resources owned by SMEs. These resources need support from human resource management, because it is a business strategy that effectively supports innovation. This study aims to determine the effect of flexible human resources, innovative work behavior and SME innovation. Researched as many as 100 SMEs creative products spread across the province of Banten. The study used convenience sampling as a sample. The data collection technique was by distributing questionnaires by directly coming to SMEs. Analysis using smart PLS. The results of the study show that flexible resource management has a positive and significant effect on SME innovation, and on innovative work behavior. Flexible human resource management has no positive and insignificant effect on SME innovation with innovative work behavior as a mediating variable. Innovative work behavior has a positive and significant effect on SME innovation.